Effect of lath martensite submicrostructure on mechanical properties and crack propagation behaviour by in‐situ tension in 0.09C–1.7Mn–0.6Cr steel. Issue 11 (22nd June 2020) - Guo, Chengyu; Hao, Leilei; Li, Shengci; Kang, Yonglin; An, Yuguo
Abstract: The present paper was aimed at understanding the effect of lath martensite submicrostructure quenched at different austenitizing temperature on the crack propagation behaviour. Different techniques were used to characterize the details of microstructure and submicrostructure. In‐situ tensile tests with scanning electron microscope were performed to observe the propagation of the crack. The results illustrated that packet size and block size increase almost linearly with the increasing austenitizing temperature. However, austenitizing temperature has no significant effect on the size of laths. Both of the packet size and the block size match the Hall–Petch relationship well with a correlation coefficient of 0.99. In macro tensile tests and in‐situ tension, the deflection angle of crack encountered with prior austenite grain boundary is higher than 60°, while it is lower than 90° for packet boundary and 60° for block boundary. The deflection angle of crack is relevant to the interface energy of the encountered boundaries. The interface energy of prior austenite grain boundary is higher than that of packet boundary because of the component difference, while the interface energy of packet boundary is higher than that of block boundary because of larger misorientation.